Metagenomic and Transcriptomic Analyses Reveal the Differences and Associations Between the Gut Microbiome and Muscular Genes in Angus and Chinese Simmental Cattle - Zheng, Ya; Chen, Juanjuan; Wang, Xiaoxuan; Han, Ling; Yang, Yayuan; Wang, Qi; Yu, Qunli (Frontiers in Microbiology, 2022)
The differences of intramuscular fat (IMF) between Angus and Chinese Simmental are not well understood. This study aimed at deciphering these differences by analyzing the gut microbiome and intramuscular differentially expressed genes (DEGs) in the two cattle. Faeces and longissimus dorsi were collected from the two groups of animals (n = 20/group) for multiomics analysis. Metagenomics uncovered significant differences in gut microbial structure and function between the two cattle. They had similar levels of short chain fatty acids, such as acetate, propionate and butyrate, however, Chinese Simmental had higher levels of isobutyrate, isovalerate, and valerate. Transcriptomic analysis revealed that the DEGs upregulated in Chinese Simmental were mainly involved in immune and inflammatory responses, while those in Angus were associated with regulation of muscle system and myofibril. Finally, we identified 17 species, including Roseburia inulinivorans, Eubacterium rectale, and Coprococcus catus, that positively correlated to muscle and fat metabolism, e.g., MSTN, MYLPF, TNNT3, and FABP3/4. Our study unveil gut microbiome differences between Angus and Chinese Simmental and reveal significative DEGs and species related to fat metabolism as well as muscle mass and function, providing valuable guidance for the development of intervention strategies to improve meat quality.